Analysis of Sales Of Benelli Two-Wheeled Vehicles During The Covid-19 Pancemic At PT. Kars Inti Amanah, Makassar City Veterans Branch - A Putri; Hasnawi Haris; Didin Halim (Public Resource Innovation Management and Excellence, 2024)
This study aims to find out and analyze the sales of Benelli brand two-wheeled vehicles during the Covid-19 pandemic at PT. Kars Inti Amanah, Veteran Branch of Makassar City. To find out the determinant factor for sales of Benelli brand two-wheeled vehicles during the Covid-19 pandemic at PT. Kars Inti Amanah, Veteran Branch of Makassar City. The number of informants in this study was 6 people with representatives and met the criteria in this study. Data collection techniques in this study through observation, interview, and documentation methods. The data analysis technique in this study uses data condensation, data presentation, and drawing conclusions.The results of this study show that sales of Benelli two-wheeled vehicles during the Covid-19 pandemic experienced a significant decline due to the condition and ability of the seller, market conditions, capital, company organizational conditions and other factors that determine sales at PT. Kars Inti Amanah, Makassar City Veterans Branch. The determinant factors in the sale of Benelli two-wheeled vehicles are supporting factors consisting of support from the Kalla Group company, product excellence and quality, collaboration with communities of classic motorcycle lovers, good teamwork, utilization of technological advances and strategic locations. The inhibiting factors consist of direct promotion, the application of restriction rules during the Covid-19 pandemic, and the difficulty of attracting consumer interest during the Covid-19 pandemic at PT. Kars Inti Amanah, Makassar City Veterans Branch.